2016
DOI: 10.2196/jmir.6374
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Ethnic Minority Patients and the Role of Language in Telehealth Trials for Type 2 Diabetes: A Systematic Review

Abstract: BackgroundType 2 diabetes is a serious, pervasive metabolic condition that disproportionately affects ethnic minority patients. Telehealth interventions can facilitate type 2 diabetes monitoring and prevent secondary complications. However, trials designed to test the effectiveness of telehealth interventions may underrecruit or exclude ethnic minority patients, with language a potential barrier to recruitment. The underrepresentation of minorities in trials limits the external validity of the findings for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 139 publications
1
31
0
Order By: Relevance
“…Ethnic minority groups are often under-represented in trials despite being 1 in 8 of the UK population and frequently having most to gain clinically 2,3 . In a review of 12 trials for patients with type 2 diabetes, the mean percentage of South Asian recruits in eight of them was 5.5% despite South Asians representing 11.2% of the UK type 2 diabetes population 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minority groups are often under-represented in trials despite being 1 in 8 of the UK population and frequently having most to gain clinically 2,3 . In a review of 12 trials for patients with type 2 diabetes, the mean percentage of South Asian recruits in eight of them was 5.5% despite South Asians representing 11.2% of the UK type 2 diabetes population 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses showed that telehealth interventions result in a modest but significant improvement in reductions in glucose levels when compared to usual care [14,15]. In addition, two 2016 systematic reviews, one based on 111 randomized controlled trials (RCTs) and another on 55 RCTs, found that home telemonitoring significantly improves glucose management; however, less than 25% of RCTs were conducted with ethnically diverse patients, thereby diminishing the external validity of the findings [16][17][18] Polisena et al 's [19] meta-analysis of 26 studies revealed a positive effect on glucose management, noting that more research of higher methodological quality is required, recommending the inclusion of patients from diverse backgrounds to increase external validity and assess technology adaptation to optimize use among different populations [19]. Other meta-analyses on underserved populations, which conclude that home telemonitoring improves glucose management, note that studies should utilize community-based participatory research (CBPR) approaches involving patients and caregivers to develop personalized interventions to enhance persistence in usage and treatment adherence [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The standard dietary education and advice provided by mainstream health care services may not adequately address the daily challenges faced by minority patients as their cultural, social, and dietary norms and socioeconomic realities differ from that of the majority population. IT tools can provide new opportunities to make DM-related dietary education and counseling more relevant and individually tailored for patients [7,8]; however, few existing examples/initiatives have included sizeable proportions of ethnic minority patients [7,15]. There is a need to expand the evidence base for new digital health technologies that can address these needs [16] among the highest-risk, most vulnerable patient populations.…”
Section: Introductionmentioning
confidence: 99%